Identification of antioxidants in Momordica charantia fruit using GC-MS metabolomics approach - Perumal, Vikneswari; Uzir, Bisha Fathamah; Abas, Faridah; Ahmed, Qamar Uddin; Nik Yusoff, Nik Mohd. Idris; Khatib, Alfi (2016)
Momorica charantia fruit is one of the herbal plants and food used in Malaysia known as “Peria katak”. This plant has been used traditionally to relieve some disease including diabetes, ulcer, gout, and cough. This study focused on the identification of potential antioxidants in this fruit using GC-MS based metabolomics approach. Six series of solvents including water, 40%, 60%, 80% ethanol in water, and ethanol was used to extract the fruit. GC-MS profiles combined with antioxidant activities (DPPH and FRAP) were calculated using orthogonal partial least square to identify which retention times in GC-MS chromatogram correlate to antioxidant activities. This information was submitted to the NIST database to elucidate which compounds were present. The score plot showed an obvious and remarkable separation into six clusters indicating the six different of metabolite profile of the extracts. The results revealed 8 compounds in this fruit induce the antioxidant activities, while 2 others suppress the bio-activities.